2023
DOI: 10.1001/jamapsychiatry.2022.4965
|View full text |Cite
|
Sign up to set email alerts
|

Association of Familial Aggregation of Major Depression With Risk of Major Depression

Abstract: ImportanceMajor depression (MD) aggregates within families, but how family history of MD confers risk of MD over the life course is unclear. Such knowledge is important to identify and prevent possible depressogenic effects of family environment.ObjectiveTo examine the association between family MD history and risk of MD including association with age, sex, type of kinship, and age of the affected family member.Design, Setting, and ParticipantsThis cohort study included all Danish citizens born from 1960 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Our results reveal that higher maternal depression predicted higher adolescent depression, in line with previous studies [26][27][28]. We found that childhood trauma of adolescents played a mediating role in the impact of maternal depression on adolescent suicidal ideation, as others have previously reported [29,30].…”
Section: Discussionsupporting
confidence: 92%
“…Our results reveal that higher maternal depression predicted higher adolescent depression, in line with previous studies [26][27][28]. We found that childhood trauma of adolescents played a mediating role in the impact of maternal depression on adolescent suicidal ideation, as others have previously reported [29,30].…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings were reported by van Dijk et al (2021) in the Adolescent Brain Cognitive Development sample and by Josefsson et al (2019) in a Swedish cohort study. Finally, in the largest study in this area, Gronemann et al (2023) followed a sample of almost three million people (all Danish citizens born between 1960 and 2003 with known parental identity) from their fifteenth birthday until they were diagnosed with depression, censored, or reached December 31, 2018. They found that for both men and women, exposure to maternal or paternal depression was associated with a two-times higher risk for developing MDD.…”
Section: Psychiatric Diagnosismentioning
confidence: 99%
“…This places a tremendous strain on healthcare resources, making the prevention and mitigation of depression an urgent societal issue to address. Depression is not only in uenced by factors such as family environment, educational level, and marital status [5][6][7] , but an increasing body of research [8][9][10] suggests that in ammatory responses play a crucial role in the pathogenesis of depression. Depressive individuals exhibit signi cant speci city in in ammatory factors, metabolic markers, and oxidative stress in their blood compared to healthy populations [11][12] .…”
Section: Introductionmentioning
confidence: 99%